4‐Hydroxyderricin and xanthoangelol from Ashitaba (Angelica keiskei) suppress differentiation of preadiopocytes to adipocytes via AMPK and MAPK pathways. Issue 10 (16th May 2013) - Zhang, Tianshun; Sawada, Keisuke; Yamamoto, Norio; Ashida, Hitoshi
<x xml:space="preserve">Abstract</x> Scope Adipocytes differentiation is deeply involved in the onset of obesity. 4‐Hydroxyderricin (4HD) and xanthoangelol (XAG) are the chalcones that are derived from Ashitaba (Angelica keiskei). In this study, we demonstrated the inhibitory effects of these chalcones on adipocytes differentiation. Methods and results 4HD and XAG suppressed intracellular lipid accumulation by Oil red O staining at 5 μM without cytotoxicity. They inhibited adipocytes differentiation accompanied by down‐expression of adipocyte‐specific transcription factors, CCAAT/enhancer‐binding protein‐β (C/EBP‐β), C/EBP‐α, and peroxisome proliferator‐activated receptor gamma (PPAR‐γ) using RT‐PCR and Western blotting analysis. To obtain insights into the underlying mechanism, the activation of AMP‐activated protein kinase (AMPK) and mitogen‐activated protein kinase pathways was investigated. These two chalcones promoted phosphorylation of AMPK and acetyl CoA carboxylase during differentiation of 3T3‐L1 adipocytes accompanied by a decrease in glycerol‐3‐phosphate acyl transferase‐1 and an increase in carnitine palmitoyltransferase‐1 mRNA expression. These chalcones also promoted phosphorylation of extracellular signal‐regulated kinases and Jun aminoterminal kinases, but not p38. Moreover, the inhibitors for AMPK and extracellular signal‐regulated kinases abolished the chalcones‐caused down‐expression of C/EBP‐β, C/EBP‐α, and PPAR‐γ. Treatment with Jun aminoterminal kinases inhibitor abolished the down‐expression of C/EBP‐α and PPAR‐γ, but not C/EBP‐β. Conclusion 4HD and XAG inhibit adipocytes differentiation through AMPK and mitogen‐activated protein kinase pathways, resulting in the down‐expression of adipocyte‐specific transcription factors.